Members of the DIP and Dpr adhesion protein families use cis inhibition to shape neural development in Drosophila. - Nicholas C Morano; Davys H Lopez; Hagar Meltzer; Alina P Sergeeva; Phinikoula S Katsamba; Kevin D Rostam; Himanshu Pawankumar Gupta; Jordan E Becker; Bavat Bornstein; Filip Cosmanescu; Oren Schuldiner; Barry Honig; et al. (PLoS Biology)
In Drosophila, two interacting adhesion protein families, Defective proboscis responses (Dprs) and Dpr interacting proteins (DIPs), coordinate the assembly of neural networks. While intercellular DIP::Dpr interactions have been well characterized, DIPs and Dprs are often co-expressed within the same cells, raising the question as to whether they also interact in cis. We show, in cultured cells and in vivo, that DIP-α and DIP-δ can interact in cis with their ligands, Dpr6/10 and Dpr12, respectively. When co-expressed in cis with their cognate partners, these Dprs regulate the extent of trans binding, presumably through competitive cis interactions. We demonstrate the neurodevelopmental effects of cis inhibition in fly motor neurons and in the mushroom body. We further show that a long disordered region of DIP-α at the C-terminus is required for cis but not trans interactions, likely because it alleviates geometric constraints on cis binding. Thus, the balance between cis and trans interactions plays a role in controlling neural development.